(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
George Sim donated the medal referenced in the title to the Society. He describes the medal’s decoration in detail and argues that this may be a one-of-a-kind piece. He also provides some biographical details about Provost George Drummond to contextualise his donation.